KEBIJAKAN PEMBERDAYAAN PEREMPUAN DI NEGERI SULI: TINJAUAN TERHADAP PERAN PEREMPUAN DALAM PEMBANGUNAN LOKAL - Almahdali, Humairah (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
Empowerment of women has become a significant topic on both the global and national development agendas, acknowledging the crucial contributions women can make to the development process. This article aims to examine and evaluate the women's empowerment policies implemented in Negeri Suli, a region in Central Maluku, Indonesia. This study employs a qualitative approach involving interviews with policy stakeholders, community leaders, and women participating in empowerment programs. We also analyze policy documents and relevant data to comprehend the policy's implementation and impact. The research findings reveal that Negeri Suli has adopted several women's empowerment policies, including skills training programs, education initiatives, and improved access to economic resources for women. The study highlights that women's empowerment has yielded positive outcomes for local economic development and an enhancement of women's social status in the region. Women in Negeri Suli are increasingly active in social, economic, and political spheres. Nevertheless, challenges remain, including gender disparities in resource access and opportunities. Furthermore, the sustainability of women's empowerment programs needs to be ensured through long-term commitment from both the government and the local community. This study contributes to understanding the implementation of women's empowerment policies in a local context, with the hope that its findings can serve as valuable considerations for policy improvements in Negeri Suli and similar regions in Indonesia. The conclusions drawn from this research underscore the importance of continually advocating for women as agents of change in the local development process, providing a foundation for further policy discussions on women's empowerment in this area.